Influence of donor age in allogeneic stem cell transplant outcome in acute myeloid leukemia and myelodisplastic syndrome. Issue 8 (August 2015) - Bastida, J.M.; Cabrero, M.; Lopez-Godino, O.; Lopez-Parra, M.; Sanchez-Guijo, F.; Lopez-Corral, L.; Vazquez, L.; Caballero, D.; Del Cañizo, C.
Highlights Patient age did not show any significant influence in outcomes HSCT. Donor age shows better OS and DFS for patients who received hematopoietic stem cell transplantation from a younger donor (<50 years). Donor age increases TRM among patients with HLA identical donor and a higher relapse rate.